Putting Structural Budget Balances on Reliable Footing - Marcell Göttert; Timo Wollmershäuser (Wirtschaftsdienst)
Abstract The design of future fiscal rules is currently being debated in Germany and the EU. A recurring point is the calculation of the structural budget balance. In the following, we present five criteria that should be fulfilled by structural budget balances. Moreover, we analyse the expost revisions of the existing production function approach and present a surveybased method that mitigates revision problems.